PENERAPAN SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN SOSIAL MENGGUNAKAN METODE FUZZY AHP - Ahmad Musa; Mukhlisulfatih Latief; Roviana Dai (Diffusion: Journal of Systems and Information Technology, 2021)
The distribution of Sosial Assistance (BANSOS) in Molombulahe Village remains to experience various issues where its one of them is the village has yet to indicate a significant change for the recipients of Social Assistance according to the data from Central Bureau of Statistics. In addition, the process of distribution for this assistance is still redundant at two types of assistance, while the selection process for the assistance recipients is still timeconsuming in regards to data processing so that an individual may take in more than one type of Social Assistance Dealing with the previos issues, a decision support system for recipients og Social Assistance by using the implementation of Fuzzy AHP method is required which could facilitate in data collection process and decision making in determining decent recipients of Social Assistance, so that there is no mare redundancy for the Assistance distribution in molumbulahe Village. Therefore, the distribution process of Social Assistence through applying the implementation of Fuzzy AHP method in the Decision Support System of Social Assistance Recipients could help the government of Molombulahe Village in the data management for proposed recipients of Social Assistance in the assistance distribution process. Therefore, the determination of decent Social Assistance recipients could be more accurate anf right on target.Keywords Decision Support System, Social Assistence, Implementation Of Fuzzy AHP